( y - 4 ) ( y² + 4 y + 16 ) =
= y³ + 4 y² + 16 y - 4 y² - 16 y - 64 = y³ - 64
If the result is the polynomial of the form:
y³ + 4 y² + a y - 4 y² - a y - 64
a = 16
2.5y + 3x = 27
5x - 2.5y = 5
Align the variables to make solving this easier.
2.5y + 3x = 27
-2.5y + 5x = 5
You can see that the 2.5y and -2.5y cancel each other out. Then add the 3x and 5x, and 27 + 5.
3x = 27
5x = 5
8x = 32
Divide both sides by 8.
x = 4
Now input that x into one of the equations to get y.
2.5y + 3(4) = 27
2.5y + 12 = 27
2.5y = 15
y = 6
The answer to this system of equations is x = 4, y = 6. (4, 6)